PERSEPSI, KOMPETENSI DAN HAMBATAN PERAWAT DALAM PEMENUHAN SPIRITUAL CARE PASIEN: LITERATURE REVIEW - Tunny, Hasna; Saleh, Ariyanti; Rachmawaty, Rini (Universitas Tribhuwana Tunggadewi, 2022)
Spiritual care is care given to meet the spiritual needs of patients, but many patients state that they do not receive spiritual support from the medical team. This is because nurses' perceptions of spirituality and spiritual care are lacking, competence is not adequate and there are obstacles in meeting the spiritual needs of patients. So this review aims to identify the perceptions, competencies and barriers of nurses in fulfilling spiritual care. Method by Literature review research design. Search articles on PubMed, ClinicalKey for Nursing, and ProQues by keyword based on PICO. Found 1,839 articles in the period 2015-2021 (May), then screening was carried out and found 20 relevant articles to be discussed and analyzed. Results The majority of nurses have a moderate-good perception of spiritual care, nurses' competence is at a moderate-good level. Barriers found, lack of knowledge, inadequate skills, heavy workload, time constraints, lack of intimacy in providing spiritual care, cultural differences and lack of hospital management support. Conclusions nurses have positive perceptions, moderate-good competition and obstacles in fulfilling spiritual care. Spiritual care education or training is needed in order to increase self-awareness about spiritual nurses in fulfilling spiritual care for patients.